Nutritional evaluation and digestibility of pearl pineapple crop waste silage in different particle sizes - Silva, Maria Luiza de Souza e; Martins, Heytor Lemos; Mata, Jhansley Ferreira da; Vieira, Vanessa Amaro; Oliveira, Mauro dal Secco de (Seven Editora, 2023)
The cultivation of pearl pineapple, produced for sale in natura, generates a large amount of cultural remains that have the potential for use in feeding ruminants in the form of silage. The experiment aimed to evaluate the nutritional value and in vitro digestibility of pearl pineapple crop residue silage in different particle sizes. A completely randomized design was used in a 2 x 4 factorial scheme with two particle sizes (20 and 50 mm) and 4 fermentation times (30, 60, 90 and 120 days after ensiling) with 4 replications. At each fermentation time, 8 samples were collected to determine dry matter (DM), mineral matter (MM), organic matter (MO), crude protein (CP), ether extract (EE), neutral detergent fiber (NDF), acid detergent fiber (ADF), hemicellulose (HEM), total digestible nutrients (TDN), total carbohydrates (TC), non-fibrous carbohydrates (CNF) and pH values. The in vitro digestibility of dry matter, neutral detergent fiber and acid detergent fiber (DIVFDA) were determined from a test carried out in an Ankom® Ruminal Fermenter (“Daisy-II Fermenter”), in a 2 x 2 factorial scheme, with 2 fermentation times (30 and 90 days) and two particle sizes. The means of observed data for each treatment were subjected to analysis of variance and compared using the Tukey test, at a 5% probability level. There was no interaction (P>0.05) between the contents of DM, MO, CP, NDF, FDA, HEM, MM, NDT, CT and CNF, except for the content of EE and pH (P